Identifying subtypes of attitudinal learning among MOOCs learners: a latent profile analysis. (3rd April 2022) - Yu, Ji Hyun; Watson, Sunnie Lee
ABSTRACT: This study aims (1) to investigate the different motivations and perspectives for Massive Open Online Courses (MOOCs) that targeted attitudinal learning outcomes; and (2) to categorise learner profiles in regards to their perceived attitudinal learning gains. Seven hundred and ninety-six learners from three MOOCs participated in an author-developed survey that measures perceived learning gains in cognitive, affective, and behavioural learning, enrolment purpose, learning activity, and course satisfaction. Latent profile analysis suggested a three-profile solution: those with cognitively engaged (n = 426, 53.5%), overall highly engaged (n = 334, 41.9%), and behaviourally engaged (n = 36, 4.6%). We found no significant difference between profiles in enrolment purpose; however, learners in the overall highly engaged profile had a significantly higher level of course satisfaction and perceived lecture videos as the most impactful learning activity, while those in the behaviourally engaged profile valued interactive session with the instructor. The paper concludes that the choice of media and other activities in MOOCs should be carefully considered and selected to create a more inclusive learning environment to better meet the needs and interests of learners from diverse backgrounds.